Forced migration: Fragility, resilience, and policy responses - Hernandez, Manuel A.; Ecker, Olivier; Läderach, Peter; Maystadt, Jean-François (International Food Policy Research Institute, 2023)
Migration is a recurrent, complex, and multidimensional phenomenon driven by a broad set of factors. These include both “push” factors that encourage or force people to move from their current location and “pull” factors that attract people to a new location. Migration is also an important adaptation strategy and development pathway that can support livelihoods, build resilience, and protect against fragility and armed conflict. Natural barriers and policy restrictions to migration may similarly result in important welfare losses.